Timing surgery in mitral regurgitation: defining risk and optimising intervention using stress echocardiography. Issue 4 (December 2016) - Liu, Boyang; Edwards, Nicola C; Ray, Simon; Steeds, Richard P
Abstract : Mitral regurgitation (MR) is the second most common form of valvular disease requiring surgery. Correct identification of surgical candidates and optimising the timing of surgery are key in management. For primary MR, this relies upon a balance between the peri-operative risks and rates of successful repair in patients undergoing early surgery when asymptomatic with the potential risk of irreversible left ventricular dysfunction if intervention is performed too late. For secondary MR, recognition that this is a highly dynamic condition where MR severity may change is key, although data on outcomes in determining whether concomitant valve intervention is performed with revascularisation has raised questions regarding timing of surgery. There has been substantial interest in the use of stress echocardiography to risk stratify patients in mitral regurgitation. This article reviews the role of stress echocardiography in both primary and secondary mitral regurgitation and discusses how this can help clinicians tackle the challenges of this prevalent condition.